Preparation of future teachers for the introduction of digital innovation in a Rural School: problems and prospects - Olena Budnyk; Kateryna Fomin; Tetiana Nazarenko; Vira Kalabska (Universidade Federal do Norte do Tocantins, 2021)
The purpose of the article: to substantiate the urgency of the problem of providing rural schools with qualified teachers; to characterize digital innovations and their use in rural education in the conditions of COVID-19; to analyze the difficulties and prospects for preparing teachers for the use of digital technologies in distance learning in rural remote schools. The following research methods were used: analytical, empirical, and mathematical statistics. Theoretical analysis of the state of the problem in pedagogical science, in particular, the introduction of digital innovations in the educational process is outlined as a necessary condition for sustainable development of rural education. The results of an empirical study conducted among future teachers on their readiness to work in the future in rural areas are presented. A gap was revealed between young teachers' professional expectations and real school practice in remote rural schools. Emphasis was placed on the necessity to ensure cooperation between schools, parents, the public, and local businesses to improve the quality of rural education.